Wire rope mis-wrap due to wire rope “cut-in” on LEBUS drums - Shuichi NAKAYAMA; Kenta SHIMIZU; Hisao TAHARA (Nihon Kikai Gakkai ronbunshu)
The physical mechanism underlying wire rope cut-in in multilayer drums was experimentally investigated. Although the wire rope appears to be correctly spooled on the drum, hoisting the load can cut the spooling wire rope into multiple layers, leading to mis-wrap or entanglement. Such irregularities may result in rope damage or reverse winding, necessitating repairs. The hand winch testing results indicated that LEBUS drums exhibit greater resistance to cut-in compared to ungrooved drums; in particular, LEBUS drums require a lower pre-tension load to prevent cut-in than ungrooved drums. Moreover, in the LEBUS, the spooling wire rope typically cuts through in a single layer, whereas in ungrooved drums, the spooling wire rope cuts deeper through multiple layers, increasing the likelihood of entanglement or reverse winding. The simultaneous slipping of several wraps in the surface layer was observed as a contributing factor to cut-in in LEBUS drums.